2007
DOI: 10.1158/1078-0432.ccr-06-1528
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene, an Active Constituent of Blueberries, Suppresses Aberrant Crypt Foci Formation in the Azoxymethane-Induced Colon Carcinogenesis Model in Rats

Abstract: Purpose: Epidemiologic studies have linked the consumption of fruits and vegetables to reduced risk of several types of cancer. Laboratory animal model studies have provided evidence that stilbenes, phenolic compounds present in grapes and blueberries, play a role in inhibiting the risk of certain cancers. Pterostilbene, a naturally occurring stilbene from blueberries, was tested for its preventive activity against colon carcinogenesis. Experimental Design: Experiments were designed to study the inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 30 publications
(41 reference statements)
3
97
0
2
Order By: Relevance
“…2). Researchers have started to explore the anticancer effects of resveratrol derivatives in vivo (40,55,(73)(74)(75), and at least one study indicated that a tetramer of resveratrol (heyneanol) had comparable or better anticancer efficacy than did resveratrol in a mouse lung cancer model (55). However, more in vivo studies of head-to-head comparisons between resveratrol and its analogues are ongoing and no doubt will help elucidate the anticancer potential of specific compounds.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…2). Researchers have started to explore the anticancer effects of resveratrol derivatives in vivo (40,55,(73)(74)(75), and at least one study indicated that a tetramer of resveratrol (heyneanol) had comparable or better anticancer efficacy than did resveratrol in a mouse lung cancer model (55). However, more in vivo studies of head-to-head comparisons between resveratrol and its analogues are ongoing and no doubt will help elucidate the anticancer potential of specific compounds.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…For instance, 3,5-O-methylated stilbenes [pterostilbene (2l; Fig. 5) and 3-hydroxypetrostilbene] are better apoptosis-inducing agents towards several tumor cells [50,51] (Fig. 5).…”
Section: -2 Production Of Stilbene Methyl Ethersmentioning
confidence: 99%
“…In addition, pterostilbene exhibits antioxidant and anticancer properties similar to those of resveratrol (Jang et al, 1997). Pterostilbene was found to be very effective in preventing carcinogeninduced preneoplastic lesions in a mouse mammary organ culture model (Rimando et al, 2002) and it showed preventive activity against colon carcinogenesis in rats (Suh et al, 2007).…”
mentioning
confidence: 98%